Reichsparteitag Nürnberg Ansichtskarte 1937 NSDAP Propaganda Richard... - Richard Borrmeister (Wikimedia Commons, 1937)
Carte postale ancienne issue de Wikimedia Commons. Titre: Reichsparteitag Nürnberg Ansichtskarte 1937 NSDAP Propaganda Richard BORRMEISTER Verlag Photo-Hoffmann München 37-7 Schutzstaffel SS Deutschland erwache Fahne Burg Nazi Rally Nuremberg castle Postcard No known copyright restrictions. " Nuremberg Party Rally " (Reichsparteitag Nürnberg). Postcard showing parading members of the en:Schutzstaffell (SS) carrying regional standards with Deutschland erwache and swastikas | signed R. Borrmeister | published by Verlag Photo-Hoffmann, Munich | Nazi Party (NSDAP) propaganda
Droits : Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château; Carte postale